Engaging Halal Lifestyle toward Purchase Intention of Event Marketing : A Study on Car Free Day Activities in Aceh - Yusniar Yusniar; Jumadil Saputra; Yuni Gemasih Tebec; Laili suhairid (Research Collaboration Community (RCC), 2020)
This study aims to be able to test and analyze the effect of halal lifestyle, price and location on purchase intention in the activities of the Banda Aceh City Car Free Day. The method used is quantitative with Non Probability Sampling in the form of purposive sampling. The data used is primary data, which is obtained directly from the object to be studied in the form of respondents' perceptions by circulating a list of questions in the form of a questionnaire to 100 respondents. Data were analyzed using multiple linear regression statistical tools. The partial test results show that the location variable does not have a positive and significant effect on purchase intention, while the price and halal lifestyle have a positive effect on purchase intention. The simultaneous test results also show that location, price and halal lifestyle variables have a positive and significant effect on purchase intention in the Banda Aceh City Car Free Day activities.